A review of the Afrotropical jumping plant-lice of the Phacopteronidae (Hemiptera: Psylloidea) - Malenovský, Igor; Burckhardt, Daniel (Zootaxa, 2009)
The Afrotropical jumping plant-lice of the family Phacopteronidae are revised. Thirty-one species are recognized, 18 of which are described as new (Pseudophacopteron arcuatum sp. nov., P. aulmanni sp. nov., P. benguelense sp. nov., P. bicolor sp. nov., P. carapae sp. nov., P. geminum sp. nov., P. hankae sp. nov., P. hollisi sp. nov., P. khayae sp. nov., P. lautereri sp. nov., P. magnum sp. nov., P. marmoratum sp. nov., P. nigritulum sp. nov., P. serrifer sp. nov., P. sodalis sp. nov., P. stigmatum sp. nov., P. tamessei sp. nov. and P. wagneri sp. nov.); Pseudophacopteron caffrariense Capener, 1973, P. pretoriense Capener, 1973 and P. zimmermanni (Aulmann, 1912) are redescribed. A lectotype is designated for P. zimmermanni. All species are illustrated and keys for the identification of adults and fifth instar larvae are provided. Information is given on distribution, host plants and biology. Twenty-six species are associated with plants of the order Sapindales ( = Rutales), one species has been collected on Tabernaemontana stapfiana (Gentianales: Apocynaceae), and four species lack reliable host data. Sympatric occurrences of several Pseudophacopteron species on particular host species are recorded on Commiphora africana from Kenya, Dacryodes edulis from Cameroon, Ekebergia benguelensis from Angola, Khaya senegalensis from Nigeria, and Vepris nobilis from Kenya and Uganda. Two large, probably monophyletic groups are recognized within the Afrotropical Phacopteronidae.